Propagation of ribonucleic acid coliphages in gnotobiotic mice. - Ando, A (1979)
To clarify the propagation cycle of bacteriophages in their natural habitats, we tested whether animals could support ribonucleic acid (RNA) phage propagation in their intestines, using germfree mice as the test animal. Propagation of four different antigenic types of RNA phages was tested. No detectable propagation or colonization of RNA phages was observed either in germfree mice or in gnotobiotic mice infected with the F- strain of Escherichia coli. Propagation or colonization was observed when RNA phages were orally introduced into gnotobiotic mice harboring the F+ or F' strain of E. coli. These results were consistent with data for in vitro propagation experiments. Fecal titers of phages were monitored over 24 to 98 days and were found to vary from 10(5) to 10(11) plaque-forming units per g of feces. Streptomycin administration gradually led to the disappearance of bacteria and, concomitantly, the RNA phages. Phages recovered from gnotobiotic mice feces included some of novel antigenic types. The bacterial isolates recovered from gnotobiotic mice harboring F+ bacteria included the original F+ strain, strains which had become F-, and some which had become inefficient hosts for the propagation of RNA phages.